Makna "Wasath" Dalam Al-Qur'an Menurut Ibnu 'Asyur: (Studi Tafsir Tematik) - Ma'sum, Muhammad (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2024)
Abstract: This study explains how Ibnu Asyur came to interpret the “wasath” verses in Al-Tahrir wa Al-Tanwir. It also uses the method of deductive reasoning to explain to establishe the fiqh with a recognized fiqh book (Maqashid As-Syari’ah). Tunisia emerged as a modern nation with Islamic democratic principles of tolerance, solidarity, and society benevolence. This study applies thematic analysis by correlating this passage with the research question. The conclusion from this research is that scholars should exercise moderation in formulating and putting into practice the moderate interpretation and application of the traditional understanding of Islam, which is wasathiyyah. Scholars Ibnu ‘Asyur also explained that the ijma's concept that scholars applied in the field of fiqh was done so in order to, they clarified that the term "wasath" refers to the degree to which Islam permits deviation from the traditional understanding of Islam.